Financing a sustainable ocean economy - U. Rashid Sumaila (Nature Portfolio, 2021)
The ocean supports many livelihoods, but this is currently not sustainable with pressures on the climate and ecosystems. Here, in this perspective, the authors outline the barriers and solutions for financing a sustainable ocean economy.